Secreted Toxoplasma gondii molecules interfere with expression of MHC-II in interferon gamma-activated macrophages. Issue 5 (April 2015) - Leroux, Louis-Philippe; Dasanayake, Dayal; Rommereim, Leah M.; Fox, Barbara A.; Bzik, David J.; Jardim, Armando; Dzierszinski, Florence S.
Graphical abstract: Highlights: Toxoplasma gondii proteins inhibit major histocompatibility complex (MHC)-II expression in macrophages. The inhibitory molecules are linked to the parasite secretory organelles. Toxoplasma gondii excreted/secreted antigens display immunomodulatory properties. Tandem-MS analysis of excreted/secreted proteins. Abstract: The obligate intracellular protozoan parasite Toxoplasma gondii interferes with major histocompatibility complex class II antigen presentation to dampen host CD4 + T cell responses. While it is known that T. gondii inhibits major histocompatibility complex class II gene transcription and expression in infected host cells, the mechanism of this host manipulation is unknown. Here, we show that soluble parasite proteins inhibit IFNγ-induced expression of major histocompatibility complex class II on the surface of the infected cell in a dose-dependent response that was abolished by protease treatment. Subcellular fractionation of T. gondii tachyzoites revealed that the major histocompatibility complex class II inhibitory activity co-partitioned with rhoptries and/or dense granules. However, parasite mutants deleted for single rhoptries or dense granules genes ( ROP1, 4/7, 14, 16 and 18 or GRA 2–9 and 12 knock-out strains) retained the ability to inhibit expression of major histocompatibility complex class II. In addition, excreted/secreted antigens released by extracellular tachyzoites displayed immunomodulatory activity characterized by an inhibition of major histocompatibility complex class II expression, and reduced expression and release of TNFα by macrophages. Tandem MS analysis of parasite excreted/secreted antigens generated a list of T. gondii secreted proteins that may participate in major histocompatibility complex class II inhibition and the modulation of host immune functions.